Adapting the Motivation Scale for Participation in Physical Activity - Amal, C. H.; Bipin, G.; Demir, Gönül Tekkurşun (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to adapt the Motivation Scale for Participation in Physical Activity (MSPPA), originally developed by Demir and Cicioğlu, (2018) in Turkish, into English. The objective was to provide a reliable and valid tool for assessing motivation for physical activity in English-speaking populations. Materials and methods. The adaptation process involved two phases. Firstly, the MSPPA was translated from Turkish to English, back-translated, and reviewed by experts in sports science and translation. Secondly, data were collected from 224 school students in the Malappuram district, Kerala, India. The collected data were subjected to Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to validate the scale’s factors. The reliability and construct validity were assessed using appropriate statistical methods. Results. The analysis of the collected data revealed three factors in the adapted MSPPA: “Individual Causes”, “Environmental Reasons”, and “Causelessness”, corresponding to intrinsic motivation, extrinsic motivation, and amotivation, respectively. The factors identified through EFA were confirmed via CFA. The scale demonstrated reliability and construct validity in assessing motivation for physical activity in English-speaking populations. Conclusions. The adapted MSPPA was found to provide a reliable and valid instrument for assessing motivation for participation in physical activity among English-speaking individuals. This adaptation has facilitated cross-cultural research and interventions aimed at promoting physical activity and its associated benefits.